Is pollen of ragweed (Ambrosia L.) a threat to people with allergies in the Wielkopolska region? - Stach, Alicja (Biodiversity: Research and Conservation, 2006)
The strongly allergenic ragweed pollen has been detected in the air of Poznań city (W Poland), in August and September, since 1995 up to date, although this alien plant is not present in Poznań. Thus the presence of ragweed pollen in the air of Poznań is probably a result of long-distance transport. Aiming to solve this question, the purpose of the study was to analyse the variation in ragweed pollen concentration in the air of Poznań in successive years of the past decade (1995-2004) and to compare this with wind directions. By using a volumetric trap, pollen concentration was estimated. Wide variations in pollen concentration were found in the study period, ranging from 17 (in 2000) to 374 (in 1999). Peaks of pollen concentration in those months were associated with E, NE, SE, and SW wind directions. This might account for the presence of ragweed pollen in the air of Poznań, when the plant itself is absent.